2014
DOI: 10.1038/bjc.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and deaths due to colorectal malignant carcinoma: a national population-based case–control study in China

Abstract: Background:This study explored the association between smoking and colorectal malignant carcinoma (CRC) in the Chinese population at the national level for the first time.Methods:In the China Nationwide Retrospective Mortality Survey conducted during 1989–1991, 12 942 CRC cases among 1 136 336 all-cause deaths aged ⩾30 years were randomly assigned 25 884 control interviews from 325 255 surviving spouses of all-cause deaths across 103 urban and rural areas.Results:Compared with non-smokers, smoking significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Controls were randomly frequency-matched to cases based on a 1:1 ratio for each case, according to gender and 10-year age spans from 30 to over 80 years old. Finally, a total of 16 205 cases and 16 205 controls, from the northern coastal China, the northern inland China, the southern coastal China, and the southern inland China according to a traditional classification of zones (see our previous publication 27 ), were included in the analysis. We also defined two diagnostic levels, the level 1 based on autopsy, histological test, surgical operation, or clinical assessment, including imaging or substantial laboratory tests in secondary or tertiary hospitals and the level 2 based on other diagnostic evidence.…”
Section: Methodsmentioning
confidence: 99%
“…Controls were randomly frequency-matched to cases based on a 1:1 ratio for each case, according to gender and 10-year age spans from 30 to over 80 years old. Finally, a total of 16 205 cases and 16 205 controls, from the northern coastal China, the northern inland China, the southern coastal China, and the southern inland China according to a traditional classification of zones (see our previous publication 27 ), were included in the analysis. We also defined two diagnostic levels, the level 1 based on autopsy, histological test, surgical operation, or clinical assessment, including imaging or substantial laboratory tests in secondary or tertiary hospitals and the level 2 based on other diagnostic evidence.…”
Section: Methodsmentioning
confidence: 99%
“…Tobacco smoking is a well-known risk factor for many diseases, including colorectal adenomas [1,2] and colorectal cancer (CRC) [3][4][5][6][7][8]. In addition, it has been associated with increased overall [9,10] as well as CRC-specific mortality [3,11,12] in previously cancer-free individuals. With improvements in cancer therapy and a growing number of cancer survivors, it becomes increasingly important to also evaluate smoking behavior in association with prognosis among already diagnosed CRC patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is showed that the current smoking prevalence decreased mildly from 33.88% in 1984 to 28.1% in 2010 for adults aged 15 years or older in the 4 national smoking surveys in China. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%